Monocytes from patients with rheumatoid arthritis and type 2 diabetes mellitus display an increased production of interleukin (IL)-1β via the nucleotide-binding domain and leucine-rich repeat containing family pyrin 3(NLRP3)-inflammasome activation: a possible implication for therapeutic decision in these patients. (19th July 2015) - Ruscitti, P; Cipriani, P; Di Benedetto, P; Liakouli, V; Berardicurti, O; Carubbi, F; Ciccia, F; Alvaro, S; Triolo, G; Giacomelli, R
Summary: A better understanding about the mechanisms involved in the pathogenesis of type 2 diabetes mellitus (T2D) showed that inflammatory cytokines such as tumour necrosis factor (TNF) and interleukin (IL)-1β play a pivotal role, mirroring data largely reported in rheumatoid arthritis (RA). IL-1β is produced mainly by monocytes (MO), and hyperglycaemia may be able to modulate, in the cytoplasm of these cells, the assembly of a nucleotide-binding domain and leucine-rich repeat containing family pyrin (NLRP3)-inflammosome, a cytosolic multi-protein platform where the inactive pro-IL-1β is cleaved into active form, via caspase-1 activity. In this paper, we evaluated the production of IL-1 β and TNF, in peripheral blood MO of patients affected by RA or T2D or both diseases, in order to understand if an alteration of the glucose metabolism may influence their proinflammatory status. Our data showed, after 24 h of incubation with different glucose concentrations, a significantly increased production of IL-1β and TNF in all evaluated groups when compared with healthy controls. However, a significant increase of IL-1β secretion by T2D/RA was observed when compared with other groups. The analysis of relative mRNA expression confirmed these data. After 24 h of incubation with different concentrations of glucose, our results showed a significant increase in NLRP3 expression. In this work, an increased production of IL-1β by MO obtained from patients affected by both RA and T2D via NLRP3-inflammasome activation may suggest a potential IL-1β targeted therapy in these patients.